In the Practice of Plein Air, the Fine Arts Occupies an Important Place and Priority - Nazirbekova Shahnoza Batirovna (Zien Journals, 2022)
This researcher has been working on the "Graphic arts and chemistry graphics" for the students, who reflected on the idea of plenerering in painting of Uzbekistan, about the works of artists and their ability to shape their rankings. Methodological techniques are used to apply the methods of the Mustalah, which deals with organizational issues, knowledge, tension, and skills of drawing art lessons. Students from the higher educational institutions, vocational colleges, and art teachers can use this academic discourse.
Keywords: Composition; genre; harmony; Item image